Description of algorithm interaction of information flows during treatment the doctor's office equipment of the ATM - Тараненко, Елена Анатольевна; Кузьмук, Валерий Валентинович; Коваленко, Александр Сергеевич; Супруненко, Оксана Александровна (Eastern-European Journal of Enterprise Technologies, 2011)
The article deals with the practical experience applications modern method of diagnosis and therapy of the human body using the transmission of information flow through specific modulation of the carrier signal and transmitting the information flows of different physical nature - gravity, electromagnetic, weak and strong nuclear [7] and their interaction